Die ökonomische Bereichsgliederung im mittelasiatisch-kazachstanischen Raum der Sowjet-Union - Giese, Ernst (ERDKUNDE, 1973)
According to the present economic regionalization (ekonomicheskiye rayonirovaniye) of the Soviet Union, Kazakhstan and the Central Asian republics of Turkmenistan, Uzbeskistan, Tadzhikistan and Kirgizistan form two economic rayons. Although South Kazakhstan has a stronger similarity to the Central Asian republics of Turkmenistan, Uzbekistan, economic structure and maintains close economic relations with that region, South Kazakhstan does not belong to the economic rayon of Central Asia but to the economic rayon of Kazakhstan. In this paper, the reasons for this allocation are examined. Apart from purely economic factors, politico-economic, national-political and administrative aspects are taken into consideration. Primary consideration is given to the question of what status and position Central Asia and Kazakhstan hold within the Soviet Union and what economic policy is pursued by Russia in relation to this former colonial region and development area of today.